Students' perception on watching english movies to enrich their vocabulary - Mohammad Himza; Zul Amri (Universitas Negeri Padang, 2023)
Vocabulary is a word that contains a certain meaning. It can also be defined as knowledge of words that are naturally learned indirectly or taught directly. This study aims to analyze students' perceptions of watching English films to enrich their vocabulary at SMA N 12 Padang. Descriptive research was applied to this study using quantitative methods. The population of this study was students of class X in the Science and Social program at SMAN 12 Padang for the 2022/2023 academic year. In this study, descriptive analysis was used to analyze the data. First, the researcher analyzed the data from the questionnaire by classifying student responses to assess student perceptions. Based on what has been discussed, presented, and analyzed in the previous chapters, it is concluded that student perceptions are in the high category, with a score of 51% or 37 students. Based on the analysis per indicator, it was found that the attractiveness indicator was included in the very high category with a score of 53% or 38 students, the effectiveness indicator was in the high category with a value of 44% or 32 students, the relevance indicator was in the high category with a value of 46% or 33, and motivation indicators are in the high category with a score of 53% or 38 students.